2020
DOI: 10.1016/j.redox.2020.101581
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of pro-inflammatory proteins by peroxynitrite increases activation of TLR4 and NF-κB: Implications for the health effects of air pollution and oxidative stress

Abstract: Environmental pollutants like fine particulate matter can cause adverse health effects through oxidative stress and inflammation. Reactive oxygen and nitrogen species (ROS/RNS) such as peroxynitrite can chemically modify proteins, but the effects of such modifications on the immune system and human health are not well understood. In the course of inflammatory processes, the Toll-like receptor 4 (TLR4) can sense damage-associated molecular patterns (DAMPs). Here, we investigate how the TLR4 response and pro-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 92 publications
2
28
0
1
Order By: Relevance
“…Oxidative stress is the result from imbalance between reactive oxygen species (ROS) overproduction and endogenous antioxidants. Excessive ROS triggered multifarious cellular stress response, such as endoplasmic reticulum (ER) stress, inflammatory reaction, genotoxic stress and hypoxia [ [70] , [71] , [72] , [73] ]. A recent plant study found ROS induced the activation of GCN2 kinase in Arabidopsis [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is the result from imbalance between reactive oxygen species (ROS) overproduction and endogenous antioxidants. Excessive ROS triggered multifarious cellular stress response, such as endoplasmic reticulum (ER) stress, inflammatory reaction, genotoxic stress and hypoxia [ [70] , [71] , [72] , [73] ]. A recent plant study found ROS induced the activation of GCN2 kinase in Arabidopsis [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also provide evidence for the protective potential of antioxidant cosmeceuticals. Ziegler & Pöschl report about the increased pro-inflammatory potential of nitrated α-synuclein, heat shock protein 60 and high-mobility-group box 1 protein, which are relevant in neurodegenerative and cardiovascular diseases, by measuring the activation of the Toll-like receptor 4 in cultured human monocytes (THP-1) [ 19 ]. The authors employed nitrated proteins as a model of damage-associated molecular patterns that arise upon reaction of endogenous proteins with nitrogen oxide radicals from air pollution or peroxynitrite generated by immune cells in response to stimulation by solid particulate matter.…”
Section: Airborne Chemical Pollutantsmentioning
confidence: 99%
“…We also put emphasis on emerging mechanisms based on dysregulation of the circadian clock, the microbiome, epigenetic pathways and cognitive function by environmental stressors. Several articles within this Special Issue thematically cover chemical environmental stressors such as air pollution [ [18] , [19] , [20] ], nano/microplastic particles [ 21 ], other toxic environmental chemicals (e.g. heavy metals or pesticides as well as airborne secondary toxicants) [ [22] , [23] , [24] ] and the behavioral risk factor waterpipe smoking [ 25 ].…”
mentioning
confidence: 99%
“…Moreover, damage-associated molecular patterns (DAMPs) like heat shock protein 60 (HSP60), high mobility group box 1 (HMGB1), and calprotectin (S100A8/A9 hetero tetramer) can be released during immune reactions elicited by COVID-19 infection (13)(14)(15)(16). These DAMPs can activate pattern recognition receptors such as TLR2, TLR4, and RAGE (14,(16)(17)(18)(19) and generate additional positive feedback via NF-κB, as has been shown for TLR4 (Fig. 1), causing further cytokine release.…”
Section: Introductionmentioning
confidence: 99%